Pengaruh Word Of Mouth, Harga, dan Kualitas Pelayanan Terhadap Keputusan Menggunakan Layanan Maxim Kota Palembang - Ananda Ramadhani; Zuul Fitriani Umari; Oki Sania Riski (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to partially determine the effect of word of mouth (WOM), price, and service quality on decisions to use online motorcycle taxi application services maxim bike category on the masses of Palembang city. This study uses primary data with a quantitative approach. The population in this study were consumers who used the online motorcycle taxi application Maxim Bike category whose number was unknown, so sampling was carried out using the Lemeshow formula with a coverage of 96 respondents. The analysis method used in this study is validity testing, reliability, classical assumption testing, and hypothesis testing using IBM SPSS 30 statistical analysis. The results of this study indicate that word of mouth (WOM) has a positive and significant effect on decisions to use maxim bike services, price has a positive and significant effect on decisions to use maxim bike services, and service quality has a positive and significant effect on decisions to use maxim bike services.